Effect of static and multi-pulsed high pressure processing on the rheological properties, microbial and physicochemical quality, and antioxidant potential of apple juice during refrigerated storage. (October 2021) - Szczepańska, Justyna; Pinto, Carlos A.; Skąpska, Sylwia; Saraiva, Jorge A.; Marszałek, Krystian
Abstract: The influence of static and multi-pulsed high pressure processing (HPP) on the quality of raw apple juice during refrigerated storage (4 °C for 12 weeks) was evaluated. Processing at 300 MPa (three pulses; for 5 min each; 15 min in total), 450 and 600 MPa (a single pulse for 5 min) caused a greater reduction in microorganisms than a single pulse at 300 MPa for 5 min. No significant changes were observed in polygalacturonase (PG) activity. HPP treatment and storage time significantly increased apparent dynamic viscosity and turbidity, while a decrease was noted in the concentration of vitamin C. Quercetin, gallic acid, procyanidin B2 and catechin were totally degraded after the 4 th week. The antioxidant activity was strongly correlated with the total polyphenolic content (TPC) and individual polyphenols. During the 12 months of storage, each juice treated by HPP turned out to be darker as evidenced by a decrease in L* value and increasing the browning index (BI). A comparable microbial quality during 12 weeks of storage was achieved for juice treated with 300 MPa x 3 and with 600 MPa, which indicates that multi-pulsed HPP can be good alternative for juice preservation resulting in the increased of equipment working life. Highlights: Polygalacturonase was resistant under HPP and sensitive to prolonged storage. HPP treatment caused an increase in apparent dynamic viscosity and turbidity. Quercetin, gallic acid, procyanidin B2, catechin showed to be barosensitive. 300 MPa x 3 pulses resulted in similar product quality as 450 and 600 MPa.